PENGARUH KEBIJAKAN AGREEMENT ON AGRICULTURE (AOA) OLEH WORLD TRADE ORGANIZATION (WTO) TERHADAP KENAIKAN IMPOR KOPI INDONESIA TAHUN 2012 - Johan Kristo Parapat; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research describes and proves the influence of policy AgreementOn Agriculture (AoA) by the World Trade Organization (WTO) for theIndonesian coffee. AoA policy is a policy of international trade in agricultureby WTO.This research uses perspective of pluralism. Pluralist assumes that stateis not unitary actor. This study also uses international trade and internationalorganizations theory.Agreement On Agriculture (AoA) is an international treaty on trade inagriculture in the WTO context. AoA since January 1st, 1995 generally is anagreement to build a trading system that is fair and market-orientedagricultural commodities in particular. AoA commitment is based on threepillars, market access, domestic support and export subsidies. Indonesia hasjoined the WTO since 1995, therefore Indonesia is obliged to follow all therules contained in the WTO, including commitments in the AoA. This studyproves that the AoA policy gave negative impact for Indonesian agriculturalcommodities, especially coffee with increasing import coffee to Indonesia in2012.Key Words: World Trade Organization (WTO), Agreement On Agriculture (AoA),Liberalitation Of Agriculture, Coffea, Indonesia.